2021
DOI: 10.46660/ijeeg.vol12.iss1.2021.552
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Trace Elements Found in Commonly Used Vegetables Irrigated By Fresh And Waste Water in Karachi, Pakistan

Abstract: Use of municipal waste water (both treated and untreated) has now become a common practice in urban and peri-urban areas. Mostly vegetables in urban cities like Karachi are being irrigated by sewerage water. In this study a comparison of sewage and fresh water-irrigated vegetables has been made with respect to trace metals. Among commonly used vegetables, green onion, cabbage, pumpkin, eggplant, bird’s eye chili and okra were selected. Two sets of these vegetables were collected, one from local farm where irri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Different studies have addressed this issue in various cities of Pakistan i.e. in Lahore, Faisalabad, Attock ( Rashid et al., 2018 ), Sargodha ( Ahmad et al., 2019 ), in Karachi ( Shehnaz et al., 2019 ; Aziz et al., 2021 ) and Sawabi ( Ali et al., 2021 ). On the other, studies have revealed that only 2% of cities are availing wastewater treatment systems in Pakistan, whilst 80% of the cities use untreated discharge for irrigation purposes ( Ullah et al., 2018 ; Shahid et al., 2020 ; Bashir et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have addressed this issue in various cities of Pakistan i.e. in Lahore, Faisalabad, Attock ( Rashid et al., 2018 ), Sargodha ( Ahmad et al., 2019 ), in Karachi ( Shehnaz et al., 2019 ; Aziz et al., 2021 ) and Sawabi ( Ali et al., 2021 ). On the other, studies have revealed that only 2% of cities are availing wastewater treatment systems in Pakistan, whilst 80% of the cities use untreated discharge for irrigation purposes ( Ullah et al., 2018 ; Shahid et al., 2020 ; Bashir et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the key reasons behind noise pollution is traffic noise caused by auto rickshaws, heavy trucks, buses, cars, water tankers and motorcycles. A recent study from the Pakistan Council of Scientific and Industrial Research on noise pollution is really alarming which showed that traffic noise on G.T road Karachi is more than 90 Db and it is excepted to reach about 110 Db which is extremely alarming because it is much higher than ISO's average standard noise level of 70 Db (Aziz et al, 2022). The Environmental Protection Agency set the traffic noise levels limit to 85 Db as National environment quality standards.…”
Section: Environmental Pollution and Role Of Regulations (Review And ...mentioning
confidence: 99%
“…The poor quality water supplies directly impact the crops biomass, fruit quality and yields (Seleiman et al, 2021). The metal salts bio-accumulation into fruits and vegetables has been mentioned in multiple studies (Aziz et al, 2021;Atta et al, 2023). Presently, the irrigation water contents are not monitored and open irrigation has given rise to soil salinity/acidity, weeds growth, metal(oid)s retention and declined crop productivity problems.…”
Section: Introductionmentioning
confidence: 99%